A comprehensive overview of tolerogenic vaccine adjuvants and their modes of action - Arve-Butler, Sabine; Moorman, Cody Deumont (Frontiers in Immunology, 2024)
Tolerogenic vaccines represent a therapeutic approach to induce antigen-specific immune tolerance to disease-relevant antigens. As general immunosuppression comes with significant side effects, including heightened risk of infections and reduced anti-tumor immunity, antigen-specific tolerance by vaccination would be game changing in the treatment of immunological conditions such as autoimmunity, anti-drug antibody responses, transplantation rejection, and hypersensitivity. Tolerogenic vaccines induce antigen-specific tolerance by promoting tolerogenic antigen presenting cells, regulatory T cells, and regulatory B cells, or by suppressing or depleting antigen-specific pathogenic T and B cells. The design of tolerogenic vaccines vary greatly, but they all deliver a disease-relevant antigen with or without a tolerogenic adjuvant. Tolerogenic adjuvants are molecules which mediate anti-inflammatory or immunoregulatory effects and enhance vaccine efficacy by modulating the immune environment to favor a tolerogenic immune response to the vaccine antigen. Tolerogenic adjuvants act through several mechanisms, including immunosuppression, modulation of cytokine signaling, vitamin signaling, and modulation of immunological synapse signaling. This review seeks to provide a comprehensive examination of tolerogenic adjuvants currently utilized in tolerogenic vaccines, describing their mechanism of action and examples of their use in human clinical trials and animal models of disease.